## How Do You Expand \( (1-x)^3 \)?

You can Expand \( (1-x)^3 \) through formulas and simple multiplication method.

first of all, I am going to expand \( (1-x)^3 \) through the formula.

\( (a-b)^3 = a^3+3ab^2–3a^2b–b^3 \)

\( (1-x)^3 = 1^3+3 \times 1 \times x^2–3\times 1^2 \times x–x^3 \)

\( (1-x)^3 = 1+3 x^2–3x–x^3 \)

Now, I am going to expand \( (1-x)^3 \) through the Multiplication.

\( (1-x)^3 = (1-x)(1-x)(1-x) \)

\( (1-x)^3 = (1-2x+x^2)(1-x) \)

\( (1-x)^3 = (1-2x+x^2)(1-x) \)

\( (1-x)^3 = 1 \times (1-2x+x^2) – x(1-2x+x^2) \)

\( (1-x)^3 = (1-2x+x^2) – (x-2x^2+x^3) \)

\( (1-x)^3 = 1-2x+x^2 – x + 2x^2 – x^3) \)

\( (1-x)^3 = 1-3x + 3x^2 – x^3) \)

Expand Form of \( (1-x)^3 = 1-3x + 3x^2 – x^3 \)